Nurses´s role in identification of hazardous pharmacohterapy as an important factor contributing to fallsof hospitalized patients - null, null; Hajduchová, Hana; Brabcová, Iva; Tóthová, Valérie; Bártlová, Sylva; Malý, Josef (STEF92 Technology Ltd., 2018)
Pharmacotherapy can play an important role in connection with falls. According to Joint Commission Resources, pharmacotherapy constitutes the fifth most frequent cause of falls in seniors. Falls occur most frequently in connection with taking of medicines that influence stability, cognitive qualities and attention, lead to dramatic changes of blood pressure or blood sugar, have sedative effects, lead to displays of parkinsonism or damage the sight and the hearing. From the perspective of prevention of falls of hospitalized patients, the nurses' knowledge may be crucial for this issue. The goal of this paper will consist in presenting the partial outcomes of the project called Analysis of factors influencing the risk of falls - potential involvement of nurses and pharmacists in minimization of the risk, implemented by the Faculty of Health and Social Studies of the University of South Bohemia in České Budějovice and the Faculty of Pharmacy of Charles University in Hradec Králové in the Czech Republic.
Keywords: hospitalized patient; fall; hazardous pharmacotherapy; nurse